THE INFLUENCE OF FINANCIAL BEHAVIOR ON THE DECISION TO SAVING IN FORMAL FINANCIAL INSTITUTIONS (CASE STUDY OF THE SANGLAR VILLAGE COMMUNITY, RETEH DISTRICT, INDRAGIRI HILIR REGENCY) - Ahmad Baidhowi; Muhammad Fauzan; Raju Maulana (Indragiri Research Center (ingreat), 2026)
This study aims to analyze and determine the influence of financial behavior on savings decisions in formal financial institutions among the people of Sanglar Village, Reteh District, Indragiri Hilir Regency. The research method used is a quantitative approach with a survey method. The research sample consisted of 50 respondents taken from the population of Sanglar Village of 6,182 people using indicator-based observation techniques. Data were collected through a questionnaire with a Likert scale and analyzed using SmartPLS 3.2.9 software. Testing was carried out through evaluation of the outer model (validity and reliability) and the inner model (hypothesis testing). The results showed that financial behavior has a positive and significant influence on savings decisions in Sanglar Village. This is evidenced by a beta coefficient value of 4.657 and a significance value (p-value) of 0.000 (<0.05). The financial behavior variable contributed 23.8% of the influence on savings decisions, while the rest was influenced by other variables outside this study. These findings indicate that the better an individual's ability to manage income, financial planning, and spending control, the higher their tendency to save in formal financial institutions.